A study on stabilization of peat soils - Norliza, Haris (Universiti Malaysia Sarawak (UNIMAS), 2006)
Peat deposits cover of 13 % or 16,500 km2 of total land area in Sarawak and its distribution is abundance in Malaysia which is 90 % of our land is peatland with a depth of 1 m. Most of the peat soils are found on low coastal land of Sarawak. Peat soil contain high organic content but has low shear strength which problematic for construction. Thus, the study mainly focused on investigating the peat soil behaviours and to stabilize it with an addition of various binders. The binders used in this project are Portland cement and industrial by-product that is fly ash. There are three different dosage rates of binders used which are 150 kg/m3, 200 kg/m3 and 250 kg/m3. The peat soil were stabilized with four mix proportion of binders which are 100 % cement, 80 % cement and 20 % fly ash, 60 % cement and 40 % fly ash and 50 % cement and 50 % fly ash. Finally, the unconfined compressive strength tests are carried out for determination of unconfined compressive strength for 7, 14 and 28 days. The results of experimental investigation postulates strength gain increased to highest value of 535 kPa as dosage rates and curing period increased.